COMPLICATIONS OF TRACHEOSTOMY IN CHILDREN : A SYSTEMATIC REVIEW - Jeremy Stephen Hermanto; Andrew Theodorous Timothy; Mellvin Telasman (International Medical Journal Corp. Ltd, 2026)
Tracheostomy is the term that is used to describe an opening that has been created in the trachea, whereas tracheotomy is the phrase that is solely used to refer to the act of producing an incision in the trachea. Tracheostomy is a term that was first coined in the 1960s to describe an opening that had been created in the trachea. When there is a sudden or prolonged obstruction of the upper airway, a tracheostomy can be performed to help bypass the obstruction. Although tracheostomy is sometimes performed as a last-ditch effort in the treatment of severe obstructive sleep apnea, the procedure is rarely used as an initial method of treatment. A tracheostomy is performed in place of an endotracheal tube in patients who need artificial ventilation for an extended period of time. Those who have inadequate control of their secretions and suffer from chronic aspiration may benefit from having a tracheostomy performed because it gives them access to deep pulmonary suctioning. Those who are born with or develop subglottic stenosis as a result of medical treatment may be able to circumvent this obstruction with the use of a tracheostomy. The potential for complications after surgery can be divided into two groups: intraoperative and postoperative, with the latter group being further subdivided into early and late postoperative difficulties. The findings of this research point to a diverse set of potential scenarios regarding the prevalence and distribution of these issues. This article demonstrates that granulation were the most common problems that we encountered in the research that were conducted above as recently as 2017. In tracheostomized patients, death is a possible unwelcome event. Most of the time, it is unrelated to the procedure and occurs as a result of the progression of the underlying disease.